Ketahanan pangan rumah tangga, status gizi, dan prestasi belajar siswa sekolah dasar - Akhmad Sujai; Maria Goretti Adiyanti; Emy Huriyati (Jurnal Gizi Klinik Indonesia, 2013)
Background: Poverty and lack of income will cause inability of the family to provide enough and nutritious food for all the family members. Fulfillment of nutritious food will bring direct impact to nutrition status of children. Malnutrition will affect brain development and intelligence that in the long run disrupts academic achievement.Objective: To identify association between food security of the household and nutrition status with academic achievement of elementary school students at Yogyakarta Municipality.Method: The study was observational with cross sectional design. Samples were students of grade V of elementary school at Subdistrict of Gedongtengen, Yogyakarta Municipality. Data of food security of the house were obtained through interview based on questionnaire of Radimer/Cornell, nutritional status data used height for age collected by measurement, and academic achievement through secondary data, i.e. original score of final semester examination. Statistical analysis was performed by using Chi-Square and Fisher’s Exact test.Results: As much as 67.6% of the household were food insecure and 13.3% of students were stunted. Food security of the household was significantly associated with nutrition status (p=0.033) and achievement in mathematics (p=0.045). There was association between nutrition status and achievement in mathematics (p=0.035); Indonesia language (p=0.000); and combined achievement in Mathematics, Indonesia language and science (p=0.004).Conclusion: There was association between food security of the household and nutritional status with academic achievement of student. There was association between food security of the household and nutrition status.